2019
DOI: 10.1136/rapm-2018-100035
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of single dose of intravenous dexamethasone on the duration of ropivacaine axillary brachial plexus block: the randomized placebo-controlled ADEXA trial

Abstract: Background and objectivesThe effect of intravenous dexamethasone on the duration of axillary plexus block performed using ropivacaine is not described. The aim of this study is to assess the effect of intravenous dexamethasone on the duration of axillary plexus block analgesia after distal upper arm surgery.MethodsIn this prospective, randomized, placebo-controlled, double-blinded trial, consenting patients scheduled for hand or forearm surgery under ultrasound-guided axillary plexus block performed using 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…30 Intraoperative dexamethasone has also been associated with reduction in postoperative pain scores, and when used with peripheral nerve blocks, it has been demonstrated to delay postoperative intake of analgesics. 31 De Oliveira et al 32 observed that, when given in excess of 0.2 mg/kg, high-dose dexamethasone reduced postoperative opioid consumption. As with other opioid-sparing medications, methadone has several properties that mediate this effect.…”
Section: Intraoperative Medicationsmentioning
confidence: 99%
“…30 Intraoperative dexamethasone has also been associated with reduction in postoperative pain scores, and when used with peripheral nerve blocks, it has been demonstrated to delay postoperative intake of analgesics. 31 De Oliveira et al 32 observed that, when given in excess of 0.2 mg/kg, high-dose dexamethasone reduced postoperative opioid consumption. As with other opioid-sparing medications, methadone has several properties that mediate this effect.…”
Section: Intraoperative Medicationsmentioning
confidence: 99%
“…The misuse of prescribed opioids leading to the current opioid epidemic crisis has put greater emphasis on the development of non-opioid analgesic techniques to manage postoperative pain [1][2][3]. A large variety of regional anesthesia techniques have been commonly used to minimize postoperative pain [4][5][6]. In addition, several techniques (e.g., transverse abdominis plane blocks, pectoral nerve blocks, brachial plexus blocks) have been evaluated in quantitative systematic reviews [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a single dose of 8 mg of the intravenous administration of dexamethasone to ropivacaine has been found to delay the onset of postoperative pain after an axillary brachial plexus blockade [ 19 ]. However, in an axillary blockade, the perineural administration of 8 mg of dexamethasone in addition to lidocaine, bupivacaine, and epinephrine has been found to provide a longer duration of analgesia in comparison to the intravenous route [ 9 ].…”
Section: Discussionmentioning
confidence: 99%